Long-acting second-generation antipsychotics : challenges and benefits of available treatments - Munjiza Jovanović, Ana; Milenković, Danica; Miljević, Čedo (Engrami, 2025)
Long-acting injectable antipsychotics were developed in the second half of the twentieth century as an important element in the deinstitutionalization process of psychiatric patients. Today, their role is significant in improving compliance, achieving stable drug concentrations in plasma, preventing relapses, and enhancing cognitive functioning in chronic patients. Although several long-acting second- and third-generation antipsychotic preparations have been registered over the past two decades, only four preparations are currently registered in our region: long-acting risperidone microspheres and in situ microparticle-based (ISM) formulations; paliperidone palmitate formulations for one and three months. This review aims to present their pharmacokinetics and pharmacodynamics, clinical efficacy, side effects, and challenges in titration and interchangeability of these preparations. Keywords: long-acting antipsychotics; risperidone microspheres; risperidone ISM; paliperidone palmitate.